2009
DOI: 10.3177/jnsv.55.442
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of an Isoflavone Fraction on Tumor Necrosis Factor-α-Induced Interleukin-8 Production in Human Intestinal Epithelial Caco-2 Cells

Abstract: SummaryThis study demonstrates the effect of soybean components on the tumor necrosis factor-␣ (TNF-␣ )-induced production of interleukin-8 (IL-8), one of the major inflammatory chemokines, in intestinal epithelial-like Caco-2 cells. Among the soybean components, an isoflavone fraction (IFF) suppressed the TNF-␣ -induced IL-8 secretion by Caco-2 cells in a dose-dependent manner, whereas a soyasaponin fraction and soypeptide fraction had no significant effect on TNF-␣ -induced IL-8 secretion. The IL-8 secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The phytochemical chlorogenic acid (found in many agricultural products such as coffee and apples) and its metabolite caffeic acid have been shown to reduce the secretion of the proinflammatory cytokine IL8 in the human IECs caco2, when they were stimulated with TNFα and H 2 O 2 (Zhao et al, 2008). Similar results were found for isoflavone fractions in another study (Satsu et al, 2009). Chlorogenic acid was also observed to inhibit LPS induced cyclooxygenase-2 expression in mouse macrophage cells, by suppressing NFκβ activation (Shan et al, 2009).…”
Section: Dietary Phytochemicalssupporting
confidence: 90%
“…The phytochemical chlorogenic acid (found in many agricultural products such as coffee and apples) and its metabolite caffeic acid have been shown to reduce the secretion of the proinflammatory cytokine IL8 in the human IECs caco2, when they were stimulated with TNFα and H 2 O 2 (Zhao et al, 2008). Similar results were found for isoflavone fractions in another study (Satsu et al, 2009). Chlorogenic acid was also observed to inhibit LPS induced cyclooxygenase-2 expression in mouse macrophage cells, by suppressing NFκβ activation (Shan et al, 2009).…”
Section: Dietary Phytochemicalssupporting
confidence: 90%
“…16,17 Considering the findings that anti-inflammatory substances, such as component(s) of the Mediterranean diet, soybeans, and n-3 unsaturated fatty acid found in fish oil seem to inhibit age-associated diseases, then anti-inflammatory polyamines may have a role in inhibiting the progression of age-associated disease. [18][19][20][21][22] This is supported by our finding that mice having a long-term intake of chow with polyamine concentrations two to three times higher than that of soybeans had decreased age-associated pathologic changes and increased longevity. 23,24…”
Section: Introductionsupporting
confidence: 52%
“…In IBD and colon cancer pathogenesis, IL-8 plays an important role in inducing the infiltration of neutrophiles and T cells into the intestinal mucosa (55,56). A number of studies demonstrated that treatment with 5-caffeoylquinic acid, caffeic acid and isoflavones effectively reduces the H 2 O 2 and TNF-α-induced IL-8 overproduction, as well as the overexpression of the IL-8 gene (57,58). In this study, we found that pretreatment with FME effectively attenuated the H 2 O 2 -induced IL-8 overproduction, and also reduced the mRNA expression of IL-8 in Caco-2 cells exposed to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%